Modelling of rotational multiple plain water jets for controlled removal of multi-material coatings. Issue 1 (2020) - Sanchez, Irati; Axinte, Dragos; Smith, Rob
Abstract: Plain Waterjet (PW) technology is an ideal process to remove damaged multi-layer coatings efficiently without damaging the substrate material. This paper proposes a mathematical model that calculates the jet footprint to remove multi-material coatings using a rotational multiple plain water jet nozzle accurately, with the new approach of considering the wear resistance properties of each material layer to provide a high efficiency coating removal. It has been proven that this enables controlled multi-layer aerospace coating removal avoiding alteration (i.e. erosion) of the substrate for both flat and curved target surfaces leaving them free of any coating residuals.